Elementary school students as citizen scientists: Mapping leishmaniasis risks (Revista Contexto & Educação, 2024)
This article shares the results of a study using citizen science as an investigative approach, with 7th grade students from a public school in Governador Valadares (MG), in a research project on leishmaniasis. It adopts studies on citizen science, territory and the contributions of Paulo Freire. The data was produced in conversation circles and workshops via the google my maps platform. The analysis focuses on the students' engagement as citizen scientists. The results show the identification of risk areas, learning about research and leishmaniasis. The conclusion is that it is important to carry out research into citizen science with primary school students with a view to promoting scientific education and citizen positions.
Keywords: Citizen science; Elementary School; Leishmaniasis; Governador Valadares